Legal Responses and Countermeasures to National Security Letters - Brett Weinstein (Washington University Journal of Law & Policy, 2015)
This note discusses the strategies and countermeasures available to American entities, including businesses, organizations, and individuals, to minimize or avoid exposure to National Security Letters (NSLs) as a part of a governmental national security investigation. The NSL is available to the government without judicial review or approval, and requires that a company or individual compel a recipient to produce certain types of records, all while keeping receipt of an NSL secret. Issued by the FBI and subject to five statutes, the constitutionality of NSLs is arguable. This note encourages companies to fight NSLs where the request is no longer narrowly tailored to the government’s compelling interest and the requested information is outside the scope of the NSL statutes.
Keywords: NSL; Snowden; National Security; FBI